CONCENTRATIONS OF HEAVY METALS OF IN APPLE FRUITS AROUND THE INDUSTERIAL AREA OF MITROVICA , KOSOVO - & et al., Imeri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The aim of this study is to measure the levels of heavy metals lead (Pb), cadmium (Cd), chrome (Cr), nickel (Ni), arsenic (As), zinc (Zn), copper (Cu) and iron (Fe) in apple fruits with some selected rootstock from the Mitrovica region, Kosovo. The concentrations of heavy metals in soil and apple tissue plants were determined by using atomic absorption spectrometry (AAS).  Compared with the reference site in contaminated areas, soil and plant contents of all analyzed metals are higher. The results of this study showed that different types of rootstock have different affinities for heavy metals. The average concentrations ranged from 1.85, 0.37, 6.88, 8.03, 0.05, 2.03, 4.36, 5.09 mg/kg for Pb, Cd, Cr, Ni, As, Zn, Cu and Fe with rootstock mm106.  In rootstock m26 concentrations ranged from 1.91, 0.22, 6.31, 7.06, 0.05, 3.28, 3.62, 4.35 mg/kg for Pb, Cd, Cr, Ni, As, Zn, Cu, Fe. While in m9 rootstock these values were found 1.67, 0.24, 5.36, 5.49, 0.03, 2.07, 2.39, 5.16 mg/kg for Pb, Cd, Cr, Ni, As, Zn, Cu and Fe. The highest mean levels of Cd, Cr and Ni were detected in apple fruits with mm106 rootstock. The results of this study showed that continuous industrial production of heavy metals over the years in the study area and permanent pollution were responsible for environmental pollution and particularly soil contamination resulting in high bioaccumulation of heavy metals in fruits.